In vitro sensitivity profile of Staphylococcus spp. isolated from samples in canine pyoderma in the city of Popayán - Daza Bolaños, Carmen Alicia; Celis Enríquez, Adriana; Chantre Gonzalez, Nasly; Gaviria Bejarano, Estephany (Spei Domus, 2020)
the canine pyoderma refers to bacterial contamination of the skin, caused in most cases by Staphylococcus pseudointermedius. During the last decades the Staphylococcus spp. have shown greater resistance to antimicrobials, in human and veterinary medicine. The objective of the present study was to determine the "in vitro" sensitivity profile of Staphylococcus spp. isolated in samples of canine pyoderma in the city of Popayán. 34 samples of canines diagnosed with pyoderma were collected in clinics and shelters, grown in 5% blood agar medium and incubated at 37 ° C. Isolated colonies were classified by biochemical methods: catalase, mannitol, maltose fermentation, glucose and sucrose. The sensitivity profile was evaluated by the method of diffusion in discs with the antibiotics, ceftriaxone, cephalexin, amoxicillin/clavulanic acid, doxycycline, clindamycin and sulfa/trimethoprim, classifying staphylococci as sensitive, intermediate or resistant with reference to the values ​​of the Clinical and Laboratory Standard Institute. In 38% of the cultured samples (n = 13) S. pseudointermedius, 18% (n = 6) S. epidermidis, 15% (n = 5) S. intermedius, 12% (n = 4) S. aureus was isolated and in 18% (n = 6) other staphylococci. Regarding the “in vitro” sensitivity profile, in general terms, a greater resistance to clindamycin (68%), cephalexin (68%), amoxicillin / clavulanic acid (59%) and ceftriaxone (56%) was observed. Regarding the most resistant pathogen, S. pseudointermedius showed resistance in 6/13 isolates for all antibiotics evaluated, followed by S. epidermidis with 5/6 isolates and S. intermedius with 3/5 isolates. S. aureus, S. and Staphylococcus spp. they showed the same proportion of resistant and sensitive samples within the total of isolates. The use of specific tests such as culture and antibiogram is useful to identify the causative pathogen and establish adequate antibiotic therapy.